1998
DOI: 10.1159/000029040
|View full text |Cite
|
Sign up to set email alerts
|

Psychopathological Considerations on the Relationship between Bulimia and Obsessive-Compulsive Disorder

Abstract: The relationship between eating disorders, impulse control disorders and obsessive-compulsive disorder as part of a so-called ‘obsessive-compulsive spectrum’ is discussed, with particular emphasis on the relationship between eating disorders (particularly bulimia) and obsessive-compulsive disorder. The empirical studies on comorbidity, personality and familiarity are briefly reviewed. Both similarities and differences found in personality, body image, mental rumination, fears, physical exercises, rituals, impu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…We may suggest that both anorexic and bulimic patients employ IM and OC as a means of gratifying or regulating various impulses and needs (Aragona & Vella, 1998;Claes et al, 2002;Fahy & Eisler, 1993). These findings may also support the view that these behaviors vary along two separate continuums in eatingdisorder patients (McElroy et al, 1994;Tylka & Subich, 1999;Wade, Bergin, Martin, Gillespie & Fairburn 2006), and are independent dimensions that can co-exist in both anorexics and bulimics and within the same individual (Claes et al, 2002;Davis & Karvinen, 2002;Raymond et al, 1999).…”
Section: Stated Insupporting
confidence: 58%
See 1 more Smart Citation
“…We may suggest that both anorexic and bulimic patients employ IM and OC as a means of gratifying or regulating various impulses and needs (Aragona & Vella, 1998;Claes et al, 2002;Fahy & Eisler, 1993). These findings may also support the view that these behaviors vary along two separate continuums in eatingdisorder patients (McElroy et al, 1994;Tylka & Subich, 1999;Wade, Bergin, Martin, Gillespie & Fairburn 2006), and are independent dimensions that can co-exist in both anorexics and bulimics and within the same individual (Claes et al, 2002;Davis & Karvinen, 2002;Raymond et al, 1999).…”
Section: Stated Insupporting
confidence: 58%
“…As mentioned above, an abundance of research pointed to the relations between AN and OC. As to the bulimic group, Aragona and Vella (1998) have suggested that the food preoccupation of bulimic patients is similar to obsessive-compulsive symptomatology, while Rothenberg (1986) has suggested that the high rates of OC among eating-disorder patients reflect their attempts to gain control over their impulses, anxieties, wishes and fantasies.…”
Section: Stated Inmentioning
confidence: 99%
“…Black, Goldstein, Noyes, and Blum (1994) identified this problem when noting a tendency to refer to so-called ''compulsive'' behaviors within several DSM conditions, including ED, substance abuse, and pathological gambling. Aragona and Vella (1998) re-stated this concern noting a risk of ''engendering confusion between impulses and compulsions' ' (p. 203). Since then, however, Matsunaga, Iwasaki, Yamagami, and Kaye (1999) refer to the ''obsessive pursuit of thinness'' and ''compulsive calorie counting'' of patients with AN (p. 407); Milos et al (2002) refer to the ''obsessional character'' of ED symptoms (p. 284); Sherman et al (2006) define AN as ''characterized by food-related and weight-related obsessions and compulsive dietary restrictions' ' (p. 468).…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…Much has been written on obsessive-compulsive features in AN versus more impulsive traits in BN (for reviews see Dawe & Loxton, 2004;Kaye, Bulik, Thornton, Barbarich, & Masters, 2004). However, several authors have also recognized impulsive traits in AN subjects (particularly the bingeing-purging subtype) and obsessive-compulsive symptoms in BN subjects (e.g., Aragona & Vella, 1998). Understanding the obsessive-compulsive and impulsive aspects in individuals with eating disorders may help guide treatment or allow for better prediction of outcome (Raymond et al, 1999).…”
Section: Introductionmentioning
confidence: 99%